A modified PEO-based composite solid electrolyte and preparation method thereof, and solid-state battery
By adding lithium-doped indium gallium phosphate to the PEO-based solid electrolyte, the problems of insufficient ion transport capability, crystallinity and electrical conductivity of the PEO-based solid electrolyte are solved, and the comprehensive performance of solid-state batteries is significantly improved.
Patent Information
- Application Number
- CN202510033401.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-01-09
AI Technical Summary
PEO-based solid electrolytes have problems such as limited ion transport capability, room temperature crystallization and poor conductivity, which limits the overall performance of solid-state batteries.
Lithium-doped indium gallium phosphate (InxGa(1-x)PO4:Li) is used as an inorganic filler to combine with PEO and lithium-based electrolytes, and modified PEO-based composite solid electrolytes are prepared by ball mill mixing and electrochemical lithium doping.
It effectively improves the mechanical strength, ion transport capability and conductivity of PEO-based solid electrolytes, and improves the comprehensive performance of solid-state batteries.
Smart Images

Figure CN119419342B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid electrolytes, and in particular relates to a modified PEO-based composite solid electrolyte and a preparation method thereof, and a solid-state battery. Background Art
[0002] Lithium-ion batteries have safety issues such as easy leakage, volatility, flammability, explosion, and poor thermal stability, which limit their development. Solid-state lithium-ion batteries that use solid electrolytes instead of liquid electrolytes are expected to fundamentally solve the safety problems of batteries. Polymer solid electrolytes have the advantages of high safety, good flexibility, easy processing into films, and excellent interface contact. Commonly used polymer matrices include polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinyl pyrrolidone (PVP), and polymethyl methacrylate (PMMA).
[0003] PEO has been widely studied in solid electrolytes due to its good film-forming properties, low glass transition temperature (Tg), and ability to dissolve a variety of lithium salts. It is currently considered one of the most competitive solid electrolyte materials. However, PEO polymers have problems such as limited ion transport capacity, room temperature crystallization, and poor conductivity. Therefore, improving the ion transport capacity, crystallinity, and conductivity of PEO-based polymer electrolytes is of great significance for further improving the overall performance of solid-state batteries. Summary of the invention
[0004] The purpose of the present invention is to provide a modified PEO-based composite solid electrolyte with good ion transmission capability and strong conductivity, a preparation method thereof, and a solid-state battery.
[0005] In the first aspect, the present invention provides a modified PEO-based composite solid electrolyte, which adopts the following technical solution:
[0006] A modified PEO-based composite solid electrolyte, comprising: lithium-doped indium gallium phosphate, PEO and a lithium-based electrolyte; wherein: the chemical formula of lithium-doped indium gallium phosphate is In x Ga (1-x) PO4:Li, 0.3≤x≤0.8.
[0007] Preferably, the lithium-based electrolyte is one or more of LiTFSI, LiFSI, and LiBF4.
[0008] Preferably, the ratio of the mass of the lithium-doped indium gallium phosphate to the total mass of PEO and the lithium-based electrolyte is (5-15):100.
[0009] Preferably, the ratio of the molar number of the repeating unit in the PEO to the molar number of the lithium-based electrolyte is (15-20):1.
[0010] The structural formula of PEO is ; The repeating unit is OCH2CH2.
[0011] In a second aspect, the present invention provides a method for preparing a modified PEO-based composite solid electrolyte, comprising the following steps:
[0012] In x Ga (1-x) PO4:Li, PEO and lithium-based electrolyte are ball-milled to obtain mixed powder; a dispersant is added to the mixed powder, and a slurry is obtained after grinding; the slurry is coated on a bottom plate, and after drying, a modified PEO-based composite solid electrolyte is obtained.
[0013] Preferably, the In x Ga (1-x) The preparation method of PO4:Li comprises the following steps:
[0014] (1) dissolving a gallium source and an indium source in water to obtain a metal salt solution; dropping phosphoric acid into the metal salt solution to perform a coprecipitation reaction to obtain an indium gallium phosphate precursor material; sintering the indium gallium phosphate precursor material to obtain indium gallium phosphate;
[0015] (3) adding a dispersant to the indium gallium phosphate in step (1), grinding, and obtaining a slurry; coating the slurry on a metal foil, and drying to obtain a negative electrode plate; connecting the negative electrode plate, the counter electrode, and the lithium-based electrolyte solution to an electrochemical workstation to perform an electrochemical discharge lithium insertion reaction, and after the reaction is completed, collecting the material on the negative electrode plate to obtain InGaPO. x Ga (1-x) PO4:Li.
[0016] Preferably, in step (1), the gallium source is one or both of gallium sulfate and gallium nitrate; and the indium source is one or both of indium nitrate and indium sulfate.
[0017] Preferably, in step (1), the phosphoric acid is concentrated phosphoric acid with a mass fraction of 65-95%; the gallium source, the indium source and the phosphoric acid are in the ratio of Ga, In and PO4 3- The molar ratio of added is x:(1-x):1, wherein: 0.3≤x≤0.8.
[0018] Preferably, in step (1), the concentration of the gallium source in water is 0.3-0.7 mol / L; the concentration of the indium source in water is 0.3-0.7 mol / L.
[0019] Preferably, in step (1), the coprecipitation reaction time is 6 to 10 hours; and the sintering temperature is 500 to 700°C.
[0020] Preferably, in step (2), the dispersant is one or more of N-methylpyrrolidone, acetonitrile and tetrahydrofuran.
[0021] Preferably, in step (2), the counter electrode is a metal lithium sheet.
[0022] Preferably, in step (2), the lithium-based electrolyte solution is one of LiTFSI, LiFSI, and LiBF4 solutions; the concentration of the lithium-based electrolyte is 1-2 mol / L; and the solvent of the lithium-based electrolyte solution is one or more of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC).
[0023] Preferably, in step (2), the voltage of the electrochemical discharge lithium insertion reaction is 0.01-3 V; the coating thickness of the indium gallium phosphate material on the metal foil is 0.1-0.2 mm; and the time of the electrochemical discharge lithium insertion reaction is 0.5-3 h.
[0024] Preferably, the dispersant is one or more of acetonitrile, tetrahydrofuran and N,N-dimethylformamide, and the mass volume ratio of PEO to the dispersant is 1 g: (10-30) mL.
[0025] Preferably, the drying is vacuum drying, the drying temperature is 70-90° C., and the drying time is 6-12 hours.
[0026] In a third aspect, the present invention provides a solid-state battery, the electrolyte of which adopts the aforementioned modified PEO solid-state electrolyte.
[0027] The above one or more technical solutions of the present invention can achieve at least one of the following beneficial effects:
[0028] (1) Indium gallium phosphate has an amorphous structure and exhibits excellent lithium ion transmission and electrical conductivity. After further embedding lithium ions in the amorphous structure of indium gallium phosphate, the lithium ion conductivity of indium gallium phosphate can be further improved, and more active sites can be provided for the transmission of lithium ions. The present invention adds lithium-doped indium gallium phosphate as an inorganic filler to the PEO-based solid electrolyte, which can effectively improve the mechanical strength, ion transmission ability and electrical conductivity of the PEO-based solid electrolyte.
[0029] (2) The present invention first synthesizes indium gallium phosphate material by a one-step coprecipitation method combined with a high-temperature sintering method, then synthesizes lithium-doped indium gallium phosphate by electrochemical lithium doping, and then composites it with the main component of the solid electrolyte PEO and a lithium-based electrolyte to finally form a lithium-doped indium gallium phosphate modified PEO-based composite solid electrolyte. The preparation process of the present invention is simple, the process is short, the raw materials are easily available, no toxic or harmful substances are generated during the preparation process, and it is easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a cycle performance diagram of the solid-state battery assembled with the modified PEO-based composite solid electrolyte in Examples 1 to 5.
[0031] Figure 2 This is a cycle performance diagram of the solid-state battery assembled with the modified PEO-based composite solid electrolyte in Examples 6 to 7.
[0032] Figure 3 This is a cycle performance diagram of the solid-state battery assembled with the PEO-based composite solid electrolyte or modified PEO-based composite solid electrolyte in Comparative Examples 1 to 4. DETAILED DESCRIPTION
[0033] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0034] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0035] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0036] The molecular weight range of PEO used in the embodiments of the present invention is 2,000,000-5,000,000.
[0037] Example 1
[0038] In the modified PEO-based solid electrolyte of this embodiment: the inorganic filler is In 0.5 Ga 0.5 PO4:Li; the lithium-based electrolyte is LiTFSI; the molecular weight of PEO is 3000000.
[0039] The specific preparation method is as follows:
[0040] (1) Dissolve 0.05 mol of gallium sulfate and 0.05 mol of indium sulfate in 100 ml of deionized water to obtain a metal salt solution; under stirring conditions, add 0.2 mol of phosphoric acid (the mass fraction of phosphoric acid is 85%) to the metal salt solution for a coprecipitation reaction for 8 hours. After filtering the reaction liquid, a filter cake is obtained; after washing the filter cake with water, alcohol and drying, an indium gallium phosphate precursor material is obtained. The indium gallium phosphate precursor material is placed in a muffle furnace and sintered at 600°C for 4 hours to obtain amorphous indium gallium phosphate.
[0041] (2) 120 mL of acetonitrile was added to 12 g of amorphous indium gallium phosphate prepared in step (1); the slurry was obtained after grinding and dispersion; the slurry was coated on copper foil (coating thickness was 0.15 mm), and after drying, it was used as a negative electrode; a lithium metal sheet was used as a counter electrode; a 1 mol / L LiTFSI solution was used as an electrolyte, and the solvent was PC; the negative electrode and the counter electrode were inserted into the electrolyte and connected to an electrochemical workstation, and then electrochemical discharge was performed at a voltage of 0.01~3 V to insert lithium for 2 h. After the lithium insertion was completed, the material on the negative electrode was scraped off the copper foil and dried to obtain InGaP. 0.5 Ga 0.5 PO4:Li.
[0042] (3) 10gIn 0.5 Ga 0.5 PO4:Li, 73.4gPEO and 26.6gLiTFSI were ball-milled and mixed to obtain a mixed powder; 2L acetonitrile was dropped into the mixed powder and the mixture was ground continuously until it was evenly dispersed to obtain a slurry. The slurry was evenly coated on a polytetrafluoroethylene plate (coating thickness was 0.22mm), and after vacuum drying at 80℃ for 8h, a modified PEO-based composite solid electrolyte was obtained.
[0043] Comparative Example 1
[0044] 73.4g PEO and 23.6g LiTFSI were ball-milled and mixed to obtain a mixed powder. 2L acetonitrile was added to the mixed powder and the mixture was ground until uniformly dispersed to obtain a slurry. The slurry was evenly coated on a polytetrafluoroethylene plate (coating thickness was 0.22mm) and dried at 80℃ under vacuum for 8h to obtain a PEO-based composite solid electrolyte.
[0045] Comparative Example 2
[0046] The same as Example 1, except that: the Li doping in step (2) is not performed; 10 g In is added in step (3) 0.5 Ga 0.5 PO4 replaces In 0.5 Ga 0.5 PO4:Li.
[0047] Comparative Example 3
[0048] The method is basically the same as Example 1, except that: in step (1), 0.1 mol of gallium sulfate is added, but indium sulfate is not added, and gallium phosphate is prepared in step (1); lithium-doped gallium phosphate GaPO4:Li is prepared in step (2); and GaPO4:Li is added in step (3) to replace In. 0.5 Ga 0.5 PO4:Li.
[0049] Comparative Example 4
[0050] The method is basically the same as Example 1, except that: in step (1), 0.1 mol indium sulfate is added without gallium sulfate, and indium phosphate is prepared in step (1); lithium-doped indium phosphate InPO4:Li is prepared in step (2); and InPO4:Li is added in step (3) to replace In. 0.5 Ga 0.5 PO4:Li.
[0051] Example 2
[0052] The method is basically the same as Example 1, except that in step (2), the electrochemical discharge is performed to insert lithium for 0.5 h.
[0053] Example 3
[0054] The method is basically the same as Example 1, except that in step (2), the electrochemical discharge is performed to insert lithium for 3 hours.
[0055] Example 4
[0056] The same as Example 1, except that: in step (3), In 0.5 Ga 0.5 The added amount of PO4:Li was 5 g.
[0057] Example 5
[0058] The same as Example 1, except that: in step (3), In 0.5 Ga 0.5 The amount of PO4:Li added was 15 g.
[0059] Example 6
[0060] In the solid electrolyte of this embodiment: the inorganic filler is In 0.4 Ga 0.6 PO4:Li; the lithium-based electrolyte is LiFSI; the molecular weight of PEO is 2000000.
[0061] The specific preparation method is as follows:
[0062] (1) Dissolve 0.04 mol of gallium nitrate and 0.06 mol of indium nitrate in 100 ml of deionized water to obtain a metal salt solution; under stirring conditions, add 0.1 mol of phosphoric acid (the mass fraction of phosphoric acid is 85%) to the metal salt solution for a coprecipitation reaction for 6 hours. After filtering the reaction liquid, a filter cake is obtained; after washing the filter cake with water, washing with alcohol and drying, an indium gallium phosphate precursor material is obtained. The indium gallium phosphate precursor material is placed in a muffle furnace and sintered at 500°C for 6 hours to obtain an amorphous indium gallium phosphate material.
[0063] (2) 120 mL of N-methylpyrrolidone was added dropwise to 12 g of amorphous indium gallium phosphate material in step (1), and the mixture was ground and dispersed uniformly to obtain a slurry; the slurry was coated on a copper foil (coating thickness was 0.1 mm), and after drying, it was used as a negative electrode; the counter electrode was a lithium metal sheet; the electrolyte was a 1 mol / L LiFSI solution, and the solvent was PC; the negative electrode and the counter electrode were inserted into the electrolyte and connected to an electrochemical workstation, and then electrochemically discharged at a voltage of 0.01 to 3 V to insert lithium for 1 h. After the lithium insertion was completed, the material on the negative electrode was scraped off the copper foil, and after drying, In 0.4 Ga 0.6 PO4:Li.
[0064] (2) 10gIn 0.4 Ga 0.6 PO4:Li, 77.9g PEO and 22.1g LiFSI were ball-milled and mixed to obtain a mixed powder; 1L tetrahydrofuran was dropped into the mixed powder, and the mixture was continuously ground until it was evenly dispersed to obtain a slurry; the slurry was evenly coated on a polytetrafluoroethylene plate (coating thickness was 0.23mm), and after vacuum drying at 70°C for 12h, a modified PEO-based composite solid electrolyte was obtained.
[0065] Example 7
[0066] In the solid electrolyte of this embodiment: the inorganic filler is In 0.7 Ga 0.3 PO4:Li; the lithium-based electrolyte is LiBF4; the molecular weight of PEO is 5000000.
[0067] The specific preparation method is as follows:
[0068] (1) Dissolve 0.07 mol of gallium sulfate and 0.03 mol of indium sulfate in 100 ml of deionized water to obtain a metal salt solution; add 0.2 mol of phosphoric acid (mass fraction of phosphoric acid is 85%) to the metal salt solution under stirring, and perform a coprecipitation reaction for 12 hours. After filtering the reaction liquid, a filter cake is obtained. After washing the filter cake with water, washing with alcohol and drying, an indium gallium phosphate precursor material is obtained. The indium gallium phosphate precursor material is placed in a muffle furnace and sintered at 700°C for 2 hours to obtain an amorphous indium gallium phosphate material.
[0069] (2) 120 mL of N-methylpyrrolidone was added dropwise to 12 g of amorphous indium gallium phosphate material in step (1), and the mixture was ground and dispersed uniformly to obtain a slurry; the slurry was coated on a copper foil (coating thickness was 0.20 mm), and after drying, it was used as a negative electrode; a lithium metal sheet was used as a counter electrode; a 2 mol / L LiBF4 solution was used as an electrolyte, and the solvent was PC; the negative electrode and the counter electrode were inserted into the electrolyte and connected to an electrochemical workstation, and then electrochemically discharged at a voltage of 0.01 to 3 V to insert lithium for 2 h. After the lithium insertion was completed, the material on the negative electrode was scraped off the copper foil, and after drying, lithium-doped indium gallium phosphate was obtained. 0.7 Ga 0.3 PO4:Li.
[0070] (3) 10gIn 0.7 Ga 0.3 PO4:Li, 90.38gPEO and 9.62gLiBF4 were ball-milled and mixed to obtain a mixed powder; 1L N,N-dimethylformamide was dropped into the mixed powder, and the mixture was ground continuously until it was evenly dispersed to obtain a slurry. The slurry was evenly coated on a polytetrafluoroethylene plate (coating thickness was 0.23mm), and after vacuum drying at 90℃ for 6h, a modified PEO-based composite solid electrolyte was obtained.
[0071] The battery assembly is completed by:
[0072] The modified PEO-based composite solid electrolyte membrane prepared in Examples 1 to 7 and Comparative Examples 1 to 4 was cut into 18 mm diameter discs as electrolyte membranes, lithium sheets were used as negative electrodes, and LiFePO4 was used as positive electrode materials to prepare positive electrode sheets; the positive electrode sheets, electrolyte membrane sheets and lithium sheets were assembled into CR2032 button batteries in a glove box. Wherein: the method for preparing LiFePO4 as a positive electrode material into a positive electrode sheet is: mixing LiFePO4: acetylene black: PVDF in a mass ratio of 8:1:1, using N-methylpyrrolidone (NMP) as a solvent, placing the mixture in a small beaker at a speed of 800 r / min and stirring the mixture for 2 hours to obtain a slurry; using an automatic coating machine to coat the slurry on a current collector aluminum foil, placing it flat on a tempered glass and transferring it to a vacuum drying oven at 85°C for drying for 4 hours, punching the sheet into a positive electrode sheet with a diameter of 12 mm, and drying it in a vacuum drying oven at 105°C for 4 hours.
[0073] After the battery is assembled and aged for 12 hours, the charge and discharge test is carried out; the battery is activated for 3 cycles at a voltage of 2.5~4.3V and a current density of 0.1C, and then cycled for 100 cycles at a current density of 1C. The test results can be seen Figures 1 to 3and Table 1 (the initial specific capacity in Table 1 is the specific capacity of the first cycle at a current density of 0.1C; the capacity retention rate is calculated based on the specific capacity of the first cycle at a current density of 1C (the 4th cycle in the figure) as the initial specific capacity).
[0074] Table 1
[0075]
[0076] from Figures 1 to 3 It can be seen from the data in Table 1 that the solid-state battery assembled with the modified PEO-based composite solid electrolyte prepared in Example 1 has good specific capacity and cycle performance. Compared with Example 1, the specific capacity and cycle performance of the solid-state battery assembled with the PEO-based composite solid electrolyte in Comparative Example 1 are significantly reduced. 0.5 Ga 0.5 The solid electrolytes were modified by PEO, GaPO4:Li, and InPO4:Li. The specific capacity and cycle performance of the solid-state batteries assembled with the corresponding modified PEO-based composite solid electrolytes were improved compared with those in Comparative Example 1, but were significantly reduced compared with those in Example 1.
[0077] The main reason for the different electrochemical discharge and lithium insertion times in Examples 1 to 3 is that the specific capacity and cycle performance of the solid-state batteries assembled with the corresponding modified PEO-based composite solid electrolytes fluctuate to a certain extent. In Example 1, the performance of the PEO-based composite solid electrolyte prepared by electrochemical discharge and lithium insertion for 2h is the best.
[0078] In Example 1, Example 4 and Example 5, the main 0.5 Ga 0.5 The specific capacity and cycle performance of the solid-state battery assembled with the modified PEO-based composite solid electrolyte prepared by the different addition amounts of PO4:Li fluctuate to a certain extent. 0.5 Ga 0.5 When the PO4:Li addition amount is 10%, the performance of the prepared PEO-based composite solid electrolyte is the best.
[0079] The main difference between Examples 6 and 7 is that the preparation process of the modified PEO-based composite solid electrolyte has certain changes, and the specific capacity and cycle stability of the corresponding assembled solid-state batteries have a certain degree of fluctuation.
[0080] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A modified PEO-based composite solid electrolyte, characterized in that: The components include: lithium-doped indium gallium phosphate, PEO and lithium-based electrolyte; wherein: the chemical formula of lithium-doped indium gallium phosphate is In x Ga (1-x) PO4:Li, 0.3≤x≤0.8; The ratio of the mass of the lithium-doped indium gallium phosphate to the total mass of PEO and the lithium-based electrolyte is (5-15):100; the ratio of the molar number of the repeating unit in PEO to the molar number of the lithium-based electrolyte is (15-20):
1.
2. The modified PEO-based composite solid electrolyte according to claim 1, characterized in that: The lithium-based electrolyte is one or more of LiTFSI, LiFSI, and LiBF4.
3. A method for preparing a modified PEO-based composite solid electrolyte according to any one of claims 1 to 2, characterized in that: The following steps are involved: In x Ga (1-x) PO4:Li, PEO and lithium-based electrolyte are ball-milled to obtain mixed powder; a dispersant is added to the mixed powder, and the mixture is ground to obtain slurry; the slurry is coated on a bottom plate, and after drying, a modified PEO-based composite solid electrolyte is obtained.
4. The method for preparing the modified PEO-based composite solid electrolyte according to claim 3, characterized in that: In x Ga (1-x) The preparation method of PO4:Li comprises the following steps: (1) dissolving a gallium source and an indium source in water to obtain a metal salt solution; dropping phosphoric acid into the metal salt solution to perform a coprecipitation reaction to obtain an indium gallium phosphate precursor material; sintering the indium gallium phosphate precursor material to obtain indium gallium phosphate; (2) adding a dispersant to the indium gallium phosphate in step (1), grinding, and obtaining a slurry; coating the slurry on a metal foil, and drying to obtain a negative electrode plate; connecting the negative electrode plate, the counter electrode, and the lithium-based electrolyte solution to an electrochemical workstation to perform an electrochemical discharge lithium insertion reaction, and after the reaction is completed, collecting the material on the negative electrode plate to obtain InGaPO. x Ga (1-x) PO4:Li.
5. The method for preparing the modified PEO-based composite solid electrolyte according to claim 4, characterized in that: In the step (1), the gallium source is one or both of gallium sulfate and gallium nitrate; the indium source is one or both of indium nitrate and indium sulfate; the indium source, gallium source and phosphoric acid are in the ratio of In, Ga and PO4 3- The molar ratio of added is x:(1-x):1, wherein: 0.3≤x≤0.
8.
6. The method for preparing the modified PEO-based composite solid electrolyte according to claim 4, characterized in that: In the step (2), the dispersant is one or more of N-methylpyrrolidone, acetonitrile and tetrahydrofuran; The counter electrode is a metal lithium sheet; The lithium-based electrolyte solution is one of LiTFSI solution, LiFSI solution and LiBF4 solution; the solvent of the lithium-based electrolyte solution is one or more of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate and ethyl methyl carbonate; The concentration of the lithium-based electrolyte is 1-2 mol / L.
7. The method for preparing a modified PEO-based composite solid electrolyte according to any one of claims 4 to 6, characterized in that: In the step (1), the coprecipitation reaction time is 6 to 10 hours; the sintering temperature is 500 to 700°C; In the step (2), the voltage range of the electrochemical discharge lithium insertion reaction is 0.01-3V; the coating thickness of the indium gallium phosphate material on the metal foil is 0.1-0.2mm; and the time of the electrochemical discharge lithium insertion reaction is 0.5-3h.
8. The method for preparing the modified PEO-based composite solid electrolyte according to claim 3, characterized in that: The dispersant is one or more of acetonitrile, tetrahydrofuran and N,N-dimethylformamide, and the mass volume ratio of PEO to the dispersant is 1g:(10-30)mL.
9. A solid-state battery, characterized in that: The modified PEO-based composite solid electrolyte according to any one of claims 1 to 2 is used.
Citation Information
Patent Citations
Laminate including active material layer and solid electrolyte layer, and all solid lithium secondary battery using it
JP2007005279A
Whole solid-type electric double layer condenser
JP2008130844A